Multi-criteria analysis of rehabilitation techniques for traditional timber frame walls in Pombalino buildings (Lisbon). (March 2018) - Stellacci, S.; Rato, V.; Poletti, E.; Vasconcelos, G.; Borsoi, G.
Abstract: This research aims to evaluate the intervention techniques currently adopted for the traditional timber frame wall, using a case study in downtown Lisbon. Different rehabilitation solutions were identified and assessed through a multi-criteria decision analysis using dedicated software (M-Macbeth, Measuring Attractiveness by a Categorical-Based Evaluation technique ). Five evaluation criteria, i.e. material compatibility and permanence, structural reliability and authenticity, and visual-tactile appearance, were selected for this specific context. A multidisciplinary panel of experts in conservation science were consulted for defining the performance descriptors, evaluation levels, and weightings of these criteria. Results show that Macbeth is a useful decision-aid capable of handling multiple outputs generated from qualitative expert judgments. Lastly, the predominance of five best-scoring interventions within three design-related scenarios is discussed. Highlights: Overview of rehabilitation techniques for traditional timber frame walls in Pombalino buildings (late 18th century); Ranking of repair and strengthening measures through a multi-criteria model; Presenting a multi-criteria procedure capable of evaluating different construction techniques within design-related scenarios; Recommendations for best rehabilitation techniques for these traditional structural components.